Pengaruh Penerapan Strategi Pembelajaran FIRE-UP terhadap Pemahaman Konsep Matematis Siswa Kelas VIII MTsN Gurun Panjang Kecamatan Bayang Kabupaten Pesisir Selatan Tahun Pelajaran 2012/2013 - ovtaleny, Mastuti; Mirna, Mirna; Zulfaneti, Zulfaneti (STKIP PGRI Sumbar, 2013)
Studentsâ mathematic larning outcome of MTsN Gurun Panjang was low. It was one of the factors that showed studentsâ mastery in mathematic concept was also low. The phenomenon was assumed due to the techer-centered situation during the teaching and learning process in he classroom. Basides, the teachers were assumed lacking in considering studentsâalready existing background knowledge, and the studentsâ mathematic concept using Fire-up strategy was higher than studentsâ mathematic concept using conventional model at grade VIII of MTsN Gurun Panjang.The design of the research was experiment. The population was students of grade VIII. The sample was taken randomly. The experiment group was VIII.1 and the control group was VIII.3. The instrument use in the researchwas essay post-test. The data was analyzed using t-test.Based on the data analysis, it was found that studentsâ average scores of experiment group was 74,04, higher that the control group the was 59. From the Minitab, it was obtained that P-value was 0.006. it showed that P-value was lower than Î±; 0,05 Therefore, it could be stated than studentsâ ability in understanding mathematic concept using Fire-Up strategy was better that students using conventional learning at grade VIII MTsN Gurun Panjang.